Standing' room only: a vintage issue in estate administration claims - Mohd Noor, Nor Azlina (UUM College of Law, Government and International Studies, 2019)
The doctrine of standing or locus standi governs the rule of competency of a person submitting their grievances to the court. A beneficiary being an incompetent plaintiff due to the lack of locus standi will not be a qualified litigant to seek the court intervention in administering deceased estate. The prevailing legal position in Malaysia is that estate beneficiaries are not authorised to bring any action against any party on behalf of the estate until and unless a sealed order of the letter of representation has been extracted. The needled issue to be discuss is whether the doctrine of standing has denied the inherent right of beneficiaries to enjoy the deceased estate. Hence, in the light of this scenario, this paper aims to analyse the tendency of the court in deciding cases relating to the standing of beneficiaries who are not personal representatives if they wish to bring claims on behalf of the estate. In this context, this paper uses the content analysis method to analyse the decided cases and relevant legal provisions. This paper concludes that Federal Court had whittled down the strict rule that beneficiaries should first obtain the grant of letters of representations of deceased’s’ estates that provide them with the locus standi of bringing any legal claims on behalf of the estates. In allowing the claims made by the beneficiaries the court acknowledged the existence of special circumstances which to be applied in a very limited manners and exceptional cases only.